Transformative Learning: Developing an E-Module Using the Canva Application for Material on Believing at the End of Days in High School - Azizah, Nur; Damayanti, Erna; Hasbi, Hasbi; Arifuddin, Arifuddin (Educational Journal of Learning Technology, 2024)
This research explores the development of e-module learning media through the Canva application, focusing on believing in the existence of the Last Day in secondary schools in Islamic religious education learning. Using the R&D (Research and Development) method and the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, this research involved class XII students at State Senior High School 4 Palopo for the 2023/2024 academic year. The findings show (1) the e-module meets essential criteria for effective Learning, (2) it shows high validity with scores of 76.32% (media), 88.33% (material), and 77.27% (language), and (3) it achieves good results. Practicality with a score of 97% (educators) and 93% (students). This e-module is deemed suitable for improving the learning process of Islamic religious education.